Study of physical losses in corn seed processing in Moghan - H.R. Gazor; A. Hamidi; R. Adelzade (علوم و فناوری بذر ایران)
In this research, cleaning, drying and grading of corn seed were investigated in Ardabil provinces (Mogan zone). Beside investigation of corn seed drying and processing machineries, some items such as moisture changes of corn seeds, broken and cracked seeds studied during process steps in four seed process factories. Although the most seed breaking belong to the large and round seeds, the most cracked seeds observed in round seeds. Cracked seeds had increasing trend and direct relationship with moisture. Numbers and revolution speed of bucket elevators had direct effect on seeds physical damages. It may increase seed cracking more than 30 percent. In totality about 15 percent of seeds go out of process line as broken seeds. Besides 30 percent of seeds cracked during process. Endosperm damages increased risk of planting and cusses to lack or poor germination.